Genetic Variation in Cadmium Accumulation and Tolerance among Wheat Cultivars at the Seedling Stage. Issue 5 (8th March 2016) - Naeem, Asif; Saifullah; Rehman, Muhammad Zia-ur; Akhtar, Tasneem; Ok, Yong Sik; Rengel, Zed
ABSTRACT: Exploitation of genetic differences to select wheat cultivars' pollution-safe from cadmium (Cd) contamination requires better understanding of Cd uptake and translocation patterns. For this purpose, 15 wheat cultivars were grown in nutrient solution and exposed to four levels of Cd, i.e., 0, 15, 30, and 45 µM. The plants were harvested after 2 weeks of Cd exposure. Root and shoot relative dry matter (DM) was decreased in most of the cultivars, but some cultivars did not exhibit any toxic symptoms. The lowest Cd concentration in shoots was recorded for Lasani-2008 and Iqbal-2000 while the highest for Sehar-2006 and Inqlab-91. Both root absorption and translocation accounted for regulating Cd concentration in shoots. There was no relationship between relative DM and Cd concentrations in roots and shoots. The results suggest that wheat cultivars with low shoot Cd concentration but higher tolerance, i.e. Lasani-2008 and Iqbal-2000, could be used in breading programs for low Cd wheat.